Shape-Persistent Tetrahedral [4+6] Boronic Ester Cages with Different Degrees of Fluoride Substitution - Elbert, Sven; Zhang, Wen-Shan; Rominger, Frank; Schröder, Rasmus R.; Mastalerz, Michael (Chemistry - a European journal, 2018)
In recent years the interest of shape-persistent organic cage compounds synthesized by dynamic covalent chemistry (DCC) has risen, because these cages are potentially interesting for gas sorption or -separation. One such reaction in DCC is the condensation of boronic acids with diols to form boronic esters. Most interestingly, the variety of geometries and sizes for boronic ester cages is much lower than that of, for example, imine-based cages. Here, a small series of shape-persistent [4+6] tetrahedral boronic ester cages is introduced. One cage has a high specific surface area of 511 m2 g−1 and selectively adsorbs ethane over ethylene and acetylene.